Growth Differentiation Factor 15 as a Biomarker for Risk Stratification in the Cardiothoracic Surgery Intensive Care Unit - Ricardo Ferreira; Tiago R. Velho; Rafael Maniés Pereira; Dora Pedroso; Beatriz Draiblate; Susana Constantino; Ângelo Nobre; Ana G. Almeida; Luís F. Moita; Fausto Pinto (Biomolecules)
Growth Differentiation Factor 15 (GDF15) is an emerging biomarker that significantly increases during acute stress responses, such as infections, and is moderately elevated in chronic and inflammation-driven conditions. While evidence suggests that high levels of GDF15 in cardiac surgery are associated with worse outcomes, its utility as an evaluator of early postoperative complications remains unclear. This study aims to characterize the postoperative profile of GDF15 in patients undergoing isolated surgical aortic valve replacement, evaluating its association with short-term outcomes. Serum samples from patients undergoing cardiac surgery were collected preoperatively and at defined postoperative time points (1 h, 6 h, 12 h, 24 h, and 48 h) to measure GDF15 levels. GDF15 levels significantly increased after surgery, peaking at 6 h. A positive correlation was observed between GDF15 levels and both cardiopulmonary bypass and aortic cross-clamp times. Notably, patients who developed postoperative acute kidney injury (AKI) or required prolonged hemodynamic support had significantly higher GDF15 levels, with increased mechanical ventilation time and extended intensive care unit length of stay. Furthermore, GDF15 levels correlated with postoperative SOFA scores at 24 h after surgery. GDF15 may be a valuable biomarker for risk stratification and guiding therapeutic decisions in cardiac surgery patients. Higher GDF15 levels were significantly associated with prolonged hemodynamic support, postoperative AKI, and measures of illness severity.